Urban Wastewater Management, Indore (M. P.) - Chetanya Mandecha; Urvashi Mahajan (Journal of Water Resources and Pollution Studies, 2025)
This comprehensive review examines in-depth wastewater analysis techniques, contaminants, treatment strategies, and their environmental impacts. The paper highlights the necessity of wastewater management for preserving water quality and the health of ecosystems by examining a variety of sampling methodologies, analytical developments, and regulatory frameworks. It serves as an essential resource for scholars, policymakers, and professionals involved in sustainable water resource management. The core of this review, on the environmental effects of wastewater toxins, explains how they harm ecosystems, human health, and water quality. The complex web of ecological disruption and potential long-term effects, such as bioaccumulation and biomagnification, is highlighted through vivid case studies. This assessment looks beyond the here and now to outline the evolving trends and challenges facing wastewater analysis in the future. A new approach to wastewater management is required, given the emergence of circular economy concepts and the threat posed by emerging contaminants. To comprehend how worldwide and local regulatory frameworks affect the development of wastewater management practices and guidelines, they are examined.